Diplomatic Activities of Rome in the VIII–III Centuries BC According to Data of the Juridical Tradition - Shmeleva, Liudmila M.; Utkina, Kseniya A.; Shmelev, Dmitry V. (Journal of History Culture and Art Research, 2018)
This paper investigates the diplomacy of the city of Rome in Royal and Early Republican periods fragmentation. It is known that the diplomatic authorities of Ancient Rome had a legal basis, fixed in Roman law. The oldest legal norms are preserved in the quotations and paraphrases of the Roman writers, lawyers and antiquaries (Cicero, Livy, Varro, Fest and others), who lived at a later time. Based on their data it is possible to reconstruct the field of public law governing the powers of fetials and ambassadors, ius gentium in the period VII - III centuries BC. In addition, they provide an opportunity to recreate some aspects of international relations in the region (relations with the Latin League, Etruscans, Volsci, Aequi and other Italian peoples) and diplomatic activities of Ancient Rome (diplomatic rituals - the Declaration of war, conclusion of peace Treaty; the position of ambassadors, diplomatic activities of the Roman Senate and consuls).